Dynamics of positive deviance in destigmatisation : celebrities and the media in the rise of veganism - Lundahl, Outi (Taylor & Francis, 2018)
How is positive deviance utilised by the news media in the destigmatisation of a consumption practice? I study this question in the context of veganism through critically informed frame analysis of a major British newspaper, the Daily Mail. This context is ideal for such an analysis as the image of veganism has been transformed in the recent years from a stigmatised lifestyle to a normalised, healthy diet. Furthermore, this transformation has particularly taken place through celebrities, who are conceptualised as positive deviants. I then develop a discursive framing perspective of the role of media in the destigmatisation process of a consumption practice. The resulting framework shows how media can use positive deviance in destigmatisation by managing both the boundaries of the stigmatised practice and the dynamics of positive deviancy. Moreover, this framework contextualises the different frames in terms of the organisational, institutional, and national context as well as macro-level ideologies.
Keywords: celebrities; destigmatisation; media; positive deviance; veganism; fi=Markkinointi|en=Marketing|